Olga Tufnell's 'Perfect Journey' Letters and photographs of an archaeologist in the Levant and Mediterranean - D.M. Green, John; Henry, Ros (UCL Press, 2021)
Olga Tufnell (1905-85) was a British archaeologist working in Egypt, Cyprus and Palestine in the 1920s and 1930s, a period often described as a golden age of archaeological discovery. For the first time, this book presents Olga's account of her experiences in her own words. Based largely on letters home, the text is accompanied by dozens of photographs that shed light on personal experiences of travel and dig life at this extraordinary time. Introductory material by John D.M. Green and Ros Henry provides the social, historical, biographical and archaeological context for the overall narrative. The letters offer new insights into the social and professional networks and history of archaeological research, particularly for Palestine under the British Mandate. They provide insights into the role of foreign archaeologists, relationships with local workers and inhabitants, and the colonial framework within which they operated during turbulent times. This book will be an important resource for those studying the history of archaeology in the Eastern Mediterranean, particularly for the sites of Qau el-Kebir, Tell Fara, Tell el-'Ajjul and Tell ed-Duweir (ancient Lachish). Moreover, Olga's lively style makes this a fascinating personal account of archaeology and travel in the interwar era.